The Development of Activity Packages to Promote Chinese Vocabulary Learning Ability using the Natural Approach for First Year Students of Bachelor of Arts Program in Chinese Faculty of Humanities and Social Sciences Chiang Mai Rajabhat University - Chuntalerkpadung, Jidapha; Kitchalarat, Kwanjai; Fuangwongsakul, Sukhansa (Journal of Education Studies, Chulalongkorn University, 2024)
The purposes of this research were 1) to study circumstances of learning management in Chinese vocabulary for first-year students of the Bachelor of Arts program in Chinese, Faculty of Humanities and Social Sciences, Chiang Mai Rajabaht University, 2) to develop activity packages to enhance Chinese vocabulary learning ability using the natural approach with the efficiency of 80/80, and 3) to analyze data of pretest and posttest learning achievement using activity packages. The sample consisted of 55 students of first-year students in first semester of the academic year 2023, selected by cluster random sampling. The research instruments were structured interviews, instruction packages, and achievement tests. Statistics used for data analysis were percentage, mean, standard deviation, and T-test. The research findings showed that 1) the circumstances of learning management in Chinese vocabulary faced challenges across various dimensions, including instructor-related issues, teaching media, assessment and evaluation methods, and student-related factors, 2) the activity packages developed had an E1/E2 efficiency of 81.82/82.36 have efficiency higher than the criteria set, and 3) the students’ learning outcomes after studying through the packages were significantly higher than before studying at .05 level. According to the results, The Development of Activity Packages to Promote Chinese Vocabulary Learning Ability using the Natural Approach is practically as the model for developing the students' learning outcomes in vocabulary for First Year Students of Bachelor of Arts Program in Chinese.